High-strength high-wear-resistance resin-based composite material and preparation method and use thereof
Patent Information
- Application Number
- CN202310609149.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-05-25
AI Technical Summary
公开号CN104212170A的专利申请公开了一种高导热耐磨聚苯硫醚复合材料及其制备方法,该发明通过填充高含量的导热填料来提高聚苯硫醚的耐磨性能和散热效果,但其对耐磨性能改善效果不稳定且力学性能不理想
[0016]实验结果表明,本发明提供树脂基复合材料具有优异的耐磨性能和力学性能,同时也表现出良好的导热效果和表面硬度,可应用于航空航天及交通运输装备、机械部件、电子电器及家用设备等领域,具有广阔的应用前景。
Smart Images

Figure CN117106305B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, specifically relating to a high-strength, high-wear-resistant resin-based composite material, its preparation method, and its applications. Background Technology
[0002] For a long time, the wear, energy loss, and product failure caused by long-term friction have had a significant impact on social and economic development. Therefore, the research and application of high wear-resistant self-lubricating composite materials have always been a cutting-edge topic in materials science and control engineering. In the past few decades, with the increasing demands for lightweight and high-performance components in engineering applications, polymer-based composite materials have been widely used in many engineering fields, especially in low-friction and wear-resistant applications, due to their unique properties.
[0003] Polyphenylene sulfide (PPS) is a polymer containing repeating p-phenylene sulfide structural units in its molecular chain. As a thermoplastic engineering plastic with excellent comprehensive properties, it possesses superior thermal stability, chemical stability, flame retardancy, physical and mechanical properties, and electrical properties, and is considered the sixth largest special engineering plastic. Furthermore, PPS resin has very low melt viscosity and excellent melt flowability, resulting in injection-molded products with excellent dimensional stability. It also exhibits strong adhesion to some metals and glass materials. Due to these numerous excellent properties, PPS and its composites have wide applications in electronics, medical, aerospace, and transportation equipment. However, PPS itself has a relatively high coefficient of friction (0.45-0.57) and specific wear rate (3.55 × 10⁻⁶). -3 mm 3 The low concentration of Nm ( / Nm) limits its application in the field of wear reduction and wear resistance.
[0004] With the development of society and economy, engineering applications have placed higher demands on the wear resistance and mechanical strength of PPS composite materials. However, most modified PPS composite materials currently available cannot simultaneously achieve excellent wear resistance and mechanical strength. For example, patent application CN114907695A discloses a composite polyphenylene sulfide material and its preparation method. This application uses grafted polytetrafluoroethylene and other solid lubricants to modify polyphenylene sulfide, but it still does not significantly improve the friction and wear performance of the composite material. Patent application CN104212170A discloses a high thermal conductivity and wear-resistant polyphenylene sulfide composite material and its preparation method. This invention improves the wear resistance and heat dissipation effect of polyphenylene sulfide by filling it with a high content of thermally conductive fillers, but its effect on improving wear resistance is unstable and its mechanical properties are not ideal. Therefore, developing a polymer-based composite material with both excellent mechanical strength and wear resistance has significant scientific value and application prospects. Summary of the Invention
[0005] The purpose of this invention is to provide a high-strength, high-wear-resistant resin-based composite material, its preparation method, and its applications. This invention uses irradiated polytetrafluoroethylene powder as a solid lubricant filler and chopped carbon fibers as a reinforcing filler. It utilizes the synergistic effect of silicon carbide nanoparticles on improving the surface hardness, thermal conductivity, and load-bearing capacity of the PPS resin-based composite material. This allows the PPS-based composite material to maintain excellent mechanical strength and heat dissipation while promoting the formation of a continuous and complete transfer film on the surface of the mating parts, thereby significantly improving the friction-reducing and wear-resistant properties of the composite material.
[0006] Specifically, this invention provides a high-strength, high-wear-resistant resin-based composite material, which is prepared from the following raw materials in parts by weight: 10-200 parts of resin matrix, 5-60 parts of solid lubricant, 1-40 parts of silicon carbide, and 5-80 parts of carbon fiber.
[0007] Furthermore, it is prepared from the following raw materials in parts by weight: 20-80 parts resin matrix, 10-40 parts solid lubricant, 5-30 parts silicon carbide, and 10-60 parts carbon fiber.
[0008] Furthermore, it is prepared from the following raw materials in parts by weight: 45.5 parts resin matrix, 19.5 parts solid lubricant, 15 parts silicon carbide, and 20 parts carbon fiber.
[0009] Furthermore, the resin matrix is a thermoplastic resin; the solid lubricant is polytetrafluoroethylene or its derivatives; the silicon carbide is irregularly shaped silicon carbide particles or spherical silicon carbide particles; and the carbon fiber is chopped carbon fiber.
[0010] Further, the thermoplastic resin is polyphenylene sulfide; the polytetrafluoroethylene derivative is irradiated modified polytetrafluoroethylene; the silicon carbide is irregularly shaped silicon carbide particles with an average particle size of 50nm-100μm; the chopped carbon fibers have an average length of 0.1-10mm and an average diameter of 1-20μm.
[0011] Furthermore, the irradiated modified polytetrafluoroethylene has a particle size of 200-300 nm; the irregularly shaped silicon carbide particles have an average particle size of 500 nm; and the chopped carbon fibers have an average length of 3 mm and an average diameter of 7 μm.
[0012] The present invention also provides a method for preparing the above-mentioned high-strength and high-wear-resistant resin-based composite material, which includes the following steps: melting and mixing the raw materials, uniformly plasticizing them, and then injection molding them to obtain the final product.
[0013] Further, the melt mixing is carried out in a twin-screw extruder, with the following temperatures in each zone: feed port temperature 180-260℃, front section of barrel temperature 220-300℃, middle section of barrel temperature 250-350℃, and rear section of barrel temperature 250-350℃; the screw speed is 20-100 r / min. Further, the injection molding is carried out in an injection molding machine, with the following temperatures in each zone:
[0014] The temperature of the front section of the barrel is 220-320℃, the temperature of the middle section of the barrel is 250-350℃, and the temperature of the rear section of the barrel is 250-350℃; the injection pressure is 50-200MPa, and the injection speed is 30-300mm / s.
[0015] The present invention also provides the use of the above-mentioned high-strength and high-wear-resistant resin-based composite material in the preparation of aerospace and transportation equipment, mechanical parts, electronic appliances and household appliances.
[0016] Experimental results show that the resin-based composite material provided by this invention has excellent wear resistance and mechanical properties, as well as good thermal conductivity and surface hardness. It can be applied to aerospace and transportation equipment, mechanical parts, electronic appliances and household appliances, and has broad application prospects.
[0017] Obviously, based on the above description of the present invention, and according to common technical knowledge and conventional methods in the field, various other modifications, substitutions or alterations can be made without departing from the basic technical concept of the present invention.
[0018] The following detailed embodiments further illustrate the above-described content of the present invention. However, this should not be construed as limiting the scope of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention. Attached Figure Description
[0019] Figure 1 Microstructures of (A) S-SiC, (B) M-SiC, (C) L-SiC, and (D) C-SiC.
[0020] Figure 2 Transient friction coefficients of PN / S20, PN / S20 / S-SiC5, PN / S20 / S-SiC10, PN / S20 / S-SiC15, PN / S20 / M-SiC15, PN / S20 / L-SiC15, and PN / S20 / C-SiC15.
[0021] Figure 3The average coefficient of friction (A) and specific wear rate (B) of PN / S20, PN / S20 / S-SiC5, PN / S20 / S-SiC10, PN / S20 / S-SiC15, PN / S20 / M-SiC15, PN / S20 / L-SiC15, and PN / S20 / C-SiC15.
[0022] Figure 4 Wear surfaces of PN / S20(A), PN / S20 / S-SiC5(B), PN / S20 / S-SiC10(C), PN / S20 / S-SiC15(D), PN / S20 / M-SiC15(E), PN / S20 / L-SiC15(F), and PN / S20 / C-SiC15(G). Detailed Implementation
[0023] The raw materials and equipment used in this invention are all known products, obtained by purchasing commercially available products.
[0024] Polyphenylene sulfide (PPS) (density 1.35 g / cm³) 3 The following materials were purchased: Irradiated polytetrafluoroethylene (PTFE) powder (JH-305F, particle size 200-300nm) purchased from Deyang Keji High-Tech Materials Co., Ltd. (melting temperature 285℃); Irradiated modified polytetrafluoroethylene (PTFE) powder (grade JH-305F, particle size 200-300nm) purchased from Sichuan Jinhe Polymer Materials Co., Ltd.; LSC070-PEEK type short-cut reinforced carbon fiber (SCF, average length 3mm, average diameter 7μm) purchased from Shanghai Lishuo Composite Materials Technology Co., Ltd.; Irregularly shaped silicon carbide nanoparticles (S-SiC, average particle size 500nm), irregularly shaped silicon carbide microparticles (M-SiC, average particle size 15μm), and large-size irregularly shaped silicon carbide particles (L-SiC, average particle size 45μm) purchased from Shanghai Buwei Applied Materials Technology Co., Ltd.; and spherical silicon carbide particles (C-SiC, average particle size 45μm) purchased from Zhejiang Yamei Nanotechnology Co., Ltd. The microstructures of all silicon carbide particles are as follows: Figure 1 As shown.
[0025] Example 1: Preparation of the high-strength, high-wear-resistant resin-based composite material of the present invention
[0026] Weigh out PPS, PTFE powder, silicon carbide, and SCF according to the proportions shown in Table 1, dry them in a forced-air drying oven at 80±5℃ for 12±0.5h, and then melt-mix them in a co-rotating parallel twin-screw extruder (TSSJ-25 / 33, Chengdu Shengda Chemical Co., Ltd.). The screw speed is set to 30r / min, and the temperatures of each zone are as follows: feed port temperature 230℃; front section of the barrel temperature 275℃, 285℃, 285℃; middle section of the barrel temperature 290℃, 290℃, 290℃; rear section of the barrel temperature 285℃, 285℃. After uniform plasticization in an extruder, cooling and granulation were carried out, followed by drying in a forced-air drying oven for 12±1 hours. Finally, injection molding was performed using a servo injection molding machine (MA2000, Ningbo Haitian Injection Molding Machine Co., Ltd.). The temperatures in each injection zone were as follows: front section of the barrel 290℃; middle section of the barrel 300℃, 300℃, 300℃; rear section of the barrel 280℃. The injection pressure was 120MPa, and the injection speed was 75mm / s. The following silicon carbide-filled modified polyphenylene sulfide composite materials were obtained: PN / S20 / S-SiC5, PN / S20 / S-SiC10, PN / S20 / S-SiC15, PN / S20 / M-SiC15, PN / S20 / L-SiC15, and PN / S20 / C-SiC15.
[0027] Table 1 Raw Material Proportions
[0028]
[0029]
[0030] The following is the method for preparing the control sample.
[0031] Comparative Example 1: Preparation of Carbon Fiber Reinforced Resin Matrix Composites
[0032] PPS, PTFE powder and SCF were weighed according to the proportions shown in Table 1, and carbon fiber reinforced resin matrix composite material was prepared according to the method in Example 1, named PN / S20.
[0033] The following experimental examples demonstrate the beneficial effects of the present invention.
[0034] Experimental Example 1: Tribological Performance Test
[0035] 1. Experimental Methods
[0036] The tribological properties of PPS-based composite materials were tested according to GB / T3960-2016 standard using an M-200 ring-block tribological testing machine (Beijing Guancheng Experimental Instrument Co., Ltd.). The sample size was 30mm*7mm*6mm. A standard steel ring was used as the friction pair, with an outer diameter of 40mm and a surface roughness (Ra) of 0.7~0.9μm. Before testing, the surface of the steel ring was polished with sandpaper, ultrasonically cleaned in acetone, and then naturally dried. The tribological properties were tested under the conditions of a sliding speed of 0.42m / s and a load of 200N (ambient temperature 20±5℃, ambient humidity 50±10%).
[0037] Field emission scanning electron microscopy (SEM) was used to observe the wear surface morphology of the composite material after friction testing.
[0038] 2. Experimental Results
[0039] Table 2. Tribological property test results
[0040]
[0041] The results show that the resin-based composite material provided by this invention has a low coefficient of friction and specific wear, exhibiting excellent friction-reducing and wear-resistant properties. The transient coefficient of friction, average coefficient of friction, and specific wear rate of each composite material are shown below. Figure 2 and Figure 3 As shown in the results, compared to PN / S20, when modified with irregularly shaped silicon carbide, only nano-sized irregularly shaped silicon carbide particles can effectively reduce the friction coefficient of the material. With the increase of silicon carbide particle size, the fluctuation of the friction coefficient and specific wear rate of the PPS composite material increases. Furthermore, with the increase of the content of nano-silicon carbide particles, the friction coefficient and specific wear rate of the composite material gradually decrease, and it can enter the friction steady state period more quickly. In addition, it is worth noting that, under the same particle size and addition amount, spherical silicon carbide particles exhibit a more efficient friction-reducing and wear-resistant effect than irregularly shaped silicon carbide particles. This shows that the micro-bearing effect of spherical particles can greatly improve the frictional behavior of the grinding surface.
[0042] Combination Figure 4 Compared to PN / S20, the wear surface morphology of the composite materials filled with irregularly shaped silicon carbide nanoparticles showed that with the increase of silicon carbide nanoparticle content, the wear surface of the composite material with irregular wear surface decreased, and was replaced by a smoother wear surface; while the wear surface of the composite material filled with spherical silicon carbide showed local large furrows and more lubricating film, resulting in relatively large wear; in addition, the wear surfaces of the composite materials filled with two different types of large-diameter irregularly shaped silicon carbide particles were severely damaged, showing poor wear resistance; the wear surface morphology of these composite materials is similar to that of PN / S20. Figure 3 The tribological properties of the composite material are corresponding.
[0043] Taking into account both the friction coefficient and specific wear rate, the wear resistance of the resin-based composite material obtained by using irregularly shaped silicon carbide particles with an average particle size of 500 nm as fillers is better than that of the composite system modified by using silicon carbide particles with an average particle size of 15 μm, 45 μm or spherical silicon carbide particles as fillers.
[0044] Experiment Example 2: Mechanical Property Testing
[0045] 1. Experimental Methods
[0046] Tensile properties were tested using an Instron 5567 universal testing machine (USA) according to GB / T1040.2-2022 standard, with sample dimensions of 150mm*10mm*4mm and a testing speed of 10mm / min. Bending properties were tested according to GB / T9341-2008 standard, with sample dimensions of 80mm*10mm*4mm and a testing speed of 2mm / min.
[0047] 2. Experimental Results
[0048] Table 3 Mechanical property test results
[0049]
[0050]
[0051] The results showed that when the SiC content was 15wt%, the flexural modulus of the resin-based composite material provided by the present invention was significantly improved compared with PN / S20, indicating that the addition of an appropriate amount of SiC particles can effectively improve the load-bearing capacity and mechanical strength of the composite material. Among them, compared with other silicon carbide-filled modification systems, the resin-based composite material PN / S20 / M-SiC15 modified with irregularly shaped silicon carbide particles with an average particle size of 15μm has the best mechanical properties.
[0052] Experimental Example 3: Shore Hardness D Test
[0053] 1. Experimental Methods
[0054] Using a HANDPILX-D Shore hardness tester (Handpi Instruments Co., Ltd., Yueqing City, China), the surface hardness of the sample was tested five times under a maximum load of 50N, and the average value was calculated. The results are shown in Table 4.
[0055] 2. Experimental Results
[0056] Table 4. Shore hardness D test results
[0057] PN / S20 84 0.7 PN / S20 / S-SiC5 85.6 0.6 PN / S20 / S-SiC10 86.2 0.8 PN / S20 / S-SiC15 87.6 0.6 PN / S20 / M-SiC15 86 0.7 PN / S20 / L-SiC15 83.8 0.5 PN / S20 / C-SiC15 83.8 0.5
[0058] The results showed that, compared with PN / S20, the surface hardness of the silicon carbide-filled modified resin matrix composites of the present invention was improved to a certain extent, except that the surface hardness of the irregularly shaped silicon carbide or spherical silicon carbide particles with an average particle size of 45 μm was slightly reduced. Among them, the PN / S20 / S-SiC15 composite exhibited the highest surface hardness. The higher surface hardness can improve the composite's ability to resist damage such as indentation and scratching of mating parts, which is beneficial to improving the tribological properties of the composite.
[0059] Experiment Example 4: Hot Disk Thermal Conductivity Test
[0060] 1. Experimental Methods
[0061] The thermal conductivity of the composite material was characterized using the transient flat-plate heat source method and a HotDisk thermal constant analyzer (2500-OT, Hot Disk, Sweden). The sample used was a flat-surfaced cube with a side length of 10 mm and a thickness of 4 mm. The sensor probe of the HotDisk instrument was placed between two regular-surfaced sample blocks and compacted to ensure full contact between the sample surface and the probe surface. The probe was then heated to a set power, allowing the generated heat to diffuse into the sample. Finally, the thermal conductivity of the sample was calculated using a fitted formula.
[0062] 2. Experimental Results
[0063] Table 5 Thermal conductivity test results
[0064] PN / S20 0.415 0.001 PN / S20 / S-SiC5 0.436 0.003 PN / S20 / S-SiC10 0.538 0.001 PN / S20 / S-SiC15 0.637 0.003 PN / S20 / M-SiC15 0.619 0.004 PN / S20 / L-SiC15 0.521 0.002 PN / S20 / C-SiC15 0.595 0.002
[0065] The results show that the thermal conductivity of the silicon carbide-filled modified resin matrix composites of this invention is significantly improved compared with PN / S20. This demonstrates that introducing silicon carbide particles can effectively improve the thermal conductivity of the composite material, which is significant for reducing heat buildup during friction. Furthermore, with S-SiC as the modified filler, the thermal conductivity of the composite material gradually increases with increasing silicon carbide content, which is related to the increased packing density of filler particles within the composite material. However, at the same content, the thermal conductivity of the composite material decreases with increasing silicon carbide particle size, indicating that the thermal conductivity of the composite material is related to the silicon carbide content and its dispersion state within the resin matrix. The PN / S20 / S-SiC15 composite material exhibits the highest thermal conductivity, which helps in the rapid dissipation of frictional heat during friction, thereby improving the tribological properties of the composite material.
[0066] In summary, the 15wt% silicon carbide nanoparticles in the silicon carbide-filled modified resin-based composite material of this invention significantly improve the surface hardness, thermal conductivity, and load-bearing capacity of the resin-based composite material. This results in the PN / S20 / S-SiC15 composite material after filling modification possessing excellent mechanical strength (tensile strength > 100 MPa, flexural strength > 150 MPa, flexural modulus > 14 GPa) and heat dissipation capacity (thermal conductivity > 0.6), while also exhibiting good resistance to damage to mating parts (surface hardness > 87). Furthermore, due to the formation of a continuous and complete transfer film on the surface of the mating parts, the composite material exhibits excellent friction-reducing and wear-resistant properties (average coefficient of friction < 0.12, specific wear rate < 4.6E-06), demonstrating optimal overall performance. This high-strength, high-wear-resistant resin-based composite material has broad application prospects in aerospace and transportation equipment, mechanical components, electronic appliances, and household appliances.
Claims
1. A high-strength, friction-reducing, and wear-resistant silicon carbide-filled modified resin-based composite material, characterized in that: It is prepared from the following raw materials in parts by weight: 45.5 parts resin matrix, 19.5 parts solid lubricant, 15 parts silicon carbide, and 20 parts carbon fiber. The resin matrix is polyphenylene sulfide; the solid lubricant is irradiated modified polytetrafluoroethylene; the silicon carbide is irregularly shaped silicon carbide particles with an average particle size of 500 nm; and the carbon fiber is chopped carbon fiber.
2. The silicon carbide-filled modified resin-based composite material according to claim 1, wherein the average length of the short-cut carbon fibers is 0.1-10 mm and the average diameter is 1-20 μm.
3. The silicon carbide-filled modified resin-based composite material according to claim 1, characterized in that: The irradiated modified polytetrafluoroethylene has a particle size of 200-300 nm; the chopped carbon fibers have an average length of 3 mm and an average diameter of 7 μm.
4. A method for preparing the high-strength, friction-reducing, and wear-resistant silicon carbide-filled modified resin-based composite material according to any one of claims 1-3, characterized in that: It includes the following steps: melting and mixing the raw materials, uniformly plasticizing them, and then injection molding them to obtain the final product.
5. The preparation method according to claim 4, characterized in that: The melt mixing is carried out in a twin-screw extruder, with the following temperatures in each zone: feed port temperature 180-260℃, front section of barrel temperature 220-300℃, middle section of barrel temperature 250-350℃, and rear section of barrel temperature 250-350℃; and the screw speed is 20-100 r / min.
6. The preparation method according to claim 4, characterized in that: The injection molding is carried out in an injection molding machine, with the following temperatures in each zone: front section of the barrel 220-320℃, middle section of the barrel 250-350℃, and rear section of the barrel 250-350℃; injection pressure 50-200 MPa, and injection speed 30-300 mm / s.
7. The use of the high-strength, friction-reducing, and wear-resistant silicon carbide-filled modified resin matrix composite material according to any one of claims 1-3 in the preparation of aerospace and transportation equipment, mechanical parts, electronic devices, and household appliances.
Citation Information
Patent Citations
High thermal conductive wear resistant polyphenylene sulfide composite material and preparation method thereof
CN104212170A
Composite polyphenylene sulfide material and preparation method thereof
CN114907695A
High-temperature-resistant self-lubricating wear-resistant composite material and preparation method thereof
CN111303629A